Analisis Kelayakan Usaha Tani Jambu Kristal Di Kelurahan Air Bang Kecamatan Curup Tengah Kabupaten Rejang Lebong - Imam Mustofa; Dwita Prisdinawati; Putri Milanda Bainamus (Politeknik Kampar, 2024)
The aims of this research are (1) To determine farmers' income from crystal guava farming. (2) To find out whether or not the Crystal guava farming business is feasible or not. One of the national fruit commodities that has great opportunities to be developed is crystal guava. Crystal guava is a fruit plant that is classified in the guava group. Guava itself is a plant that lives in tropical and sub-tropical areas, so this plant is widely cultivated in many countries, including Indonesia.Based on the table, it can be seen that the production obtained by crystal guava farmers in Air Bang sub-district during one production period is 500kg/arapan/production period or 2 tonnes/arapan/year. with a selling price of Rp. 20,000/kg. So it can be seen that the gross income obtained by crystal guava farmers in Air Bang sub-district is 10,000,000/farm/production period or IDR 40,000,000/year. The net income obtained by crystal guava farmers in the Air Bang sub-district is IDR 6,059,184 /Garapan/period or IDR 24,236,744 /Garapan/year. Bank Rakyat Indonesia's interest rate is 10%, the NVP value obtained is 28.5%. This shows that Crystal guava farming is in the Air Bang sub-district, Curup Tengah District, Rejang Lebong Regency. feasible to run NPV is positive or NPV is greater than zero (NPV > 0).